Strategi Guru dalam Menanamkan Kebiasaan Sholat Berjamaah pada Siswa di MTs Miftahul Ulum Leces Kabupaten Probolinggo - Devi Nur Azizah; Devy Habibi Muhammad; Pratiwi Dwi Warih Sitaresmi (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Teachers have a significant influence on how education is developed, especially how formal education is developed in schools. The success of students is also influenced by the teacher, especially in terms of the teaching and learning process and instilling habits that have a positive impact. The greatest contribution to high-quality educational practice and outcomes is made by teachers in the character-building process of learners. So the purpose of this research is to find out how an educator's strategy is in implementing the habit of praying in congregation at Mts Miftahul Ulum Leces, Probolinggo Regency. In this study, researchers used a qualitative descriptive method, and the approach was carried out using data analysis from the results of observations and interviews. So the results of this study the role of the Mts Miftahul Ulum Leces teacher in Probolinggo Regency in instilling congregational prayers for students has a positive impact on students to apply the habit of praying in congregation. So it can be concluded that the teacher's strategy in instilling the habit of praying in congregation of students has a very big influence on forming students' habits of praying in congregation at Mts Miftahul Ulum Leces, Probolinggo Regency.